2011
DOI: 10.1128/iai.00144-11
|View full text |Cite
|
Sign up to set email alerts
|

TREM-1 Amplifies Corneal Inflammation after Pseudomonas aeruginosa Infection by Modulating Toll-Like Receptor Signaling and Th1/Th2-Type Immune Responses

Abstract: As a novel family of cell surface receptors, triggering receptors expressed on myeloid cells (TREMs) play an important role in inflammatory responses. However, the role of TREMs in the ocular immune system remains unknown. In this study, we examined the expression and function of TREM-1 in Pseudomonas aeruginosa keratitis, one of the most common sight-threatening ocular diseases. TREM-1 was significantly increased in human corneas after P. aeruginosa infection. Consistent with TREM-1 expression at the human oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 43 publications
1
74
1
Order By: Relevance
“…Previous animal studies of TREM-1 blockade suggested that modulation of the TREM-1 pathway can decrease inflammation without sacrificing bacterial control upon infection (23)(24)(25)(26)(27)(28)(29). We initially hypothesized that TREM-1 deficiency would decrease inflammation and improve survival in a murine KPLA model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous animal studies of TREM-1 blockade suggested that modulation of the TREM-1 pathway can decrease inflammation without sacrificing bacterial control upon infection (23)(24)(25)(26)(27)(28)(29). We initially hypothesized that TREM-1 deficiency would decrease inflammation and improve survival in a murine KPLA model.…”
Section: Discussionmentioning
confidence: 99%
“…Initial findings established TREM-1 as an amplifier of the systemic inflammatory response syndrome associated with sepsis. The apparent detrimental effects of overstimulation through TREM-1 and the survival advantage of modulating TREM-1 signaling have been shown in various murine bacterial infection models (23)(24)(25)(26)(27)(28)(29). However, recent findings suggested TREM-1 signaling is necessary for successful antimicrobial responses in sepsis and pneumonia murine models (30,31), indicating that inappropriate modulation of the TREM-1 pathway could have profound effects on septic patients and may be detrimental.…”
mentioning
confidence: 96%
“…S. suis serotype 2 strain 05ZY (also known as SC-19) was isolated from the brain of a diseased piglet during the outbreak of S. suis diseases in China in 2005. The strain expresses muramidase-released protein, extracellular protein factor, and suilysin and is highly pathogenic to mice and pigs, causing STSLS (42,43). RAW264.7 mouse macrophage cells were purchased from ATCC (TIB-71) and maintained in Dulbecco's modified Eagle's medium supplemented with 10% fetal calf serum at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, the corneal scarification model involves scratching through both the corneal epithelium and the basal lamina of mouse corneas to allow bacteria direct access to the underlying corneal stroma, an event required for triggering of visible corneal pathology (keratitis). Consequently, the model is well suited to studying what occurs after bacteria have gained access into the corneal stroma, and much has been learned through its utilization for that purpose (31)(32)(33)(34)(35). Indeed, we have used it to show that the T3SS can participate in keratitis caused by P. aeruginosa (28,30,36).…”
mentioning
confidence: 99%